Deeply Contacting the Inner World of Another: Practicing Empathy in Values-Based Negotiation Role Plays - Jennifer Gerarda Brown (Washington University Journal of Law & Policy, 2012)
Teachers of law are preparing students to be peacemakers—or, at least, to facilitate peace by helping clients resolve conflict in particular ways. Much of the curriculum in law school focuses on resolving or preventing conflict in courts, legislatures, and administrative agencies. In dispute resolution classes, we strive to broaden students' understandings of the mechanisms, models, and norms by which they can assist their clients to resolve conflict. Theorists and practitioners seem to agree about the importance of this elemental—if somewhat elusive—competency. Yet, whether and how we can teach empathy continues to puzzle us. This Essay suggests one potentially fruitful tool for nurturing empathy: a series of role plays that Lawrence Susskind and I developed with David Kovick and Kate Harvey. These role plays, Williams v. Northville, Ellis v. MacroB, and Springfield OutFest, involve values-based disputes ("VBDs") in which individuals with deep convictions and religious faith essential to their core identities find themselves in conflict with institutions perceived to be hostile to their beliefs, conflicting specifically about a policy or norm that guarantees LGBT equality. This Essay adds some thoughts about the way values-based dispute simulations offer students a powerful opportunity to practice empathy. This practice comes simply in playing a character who is fully and sensitively drawn to be dramatically different from the student. In order to play the character with any kind of competence, the student must empathize with the character, must enter into his or her world view, and must respond to others' behavior as the character would. At the end of this Essay, I share some reflections from students who have participated in such role plays.
Keywords: Legal education – innovative approaches; Values-based dispute (VBD); Social skills; Negotiation; Role-play; Legal profession; Emotional development; Empathy; Law students; Client development; Psychology